ANALYSIS OF CHILDREN BORN THRU IVF IN INHERITANCE FROM THE PERSPECTIVE OF ISLAMIC LAW AND POSITIVE LAW - Riski , Mohammad; Saini (International Journal of Multidisciplinary Reseach, 2025)
The development of assisted reproductive technology, particularly In Vitro Fertilization (IVF), has raised significant legal issues in Indonesia concerning lineage (nasab) and inheritance rights of children. This study aims to analyze the legal status of IVF-born children from the perspectives of Islamic law and Indonesian positive law, with a focus on lineage legitimacy and its implications for inheritance. The research employed a library research method with a normative juridical approach, descriptive-analytical nature, and comparative analysis techniques using statutory regulations, classical fiqh, fatwas, and academic literature. The findings reveal that Islamic law permits IVF when gametes originate from a legally married couple, but prohibits third-party donors and surrogacy, as such cases result in illegitimate children without inheritance rights. In contrast, Indonesian positive law recognizes children born within lawful marriage but lacks explicit regulation regarding the use of donors or surrogate mothers, leading to a legal vacuum. This study concludes that harmonization between Islamic legal principles and positive law is essential to ensure legal certainty, safeguard the rights of IVF-born children, and prevent future inheritance disputes.